Visceral and emotional responses to direct electrical stimulations of the cortex. Issue 1 (24th November 2022) - Soulier, Hugo; Mauguière, François; Catenoix, Hélène; Montavont, Alexandra; Isnard, Jean; Hermier, Marc; Guenot, Marc; Rheims, Sylvain; Mazzola, Laure
Abstract: Objective: Visceral sensations are bodily symptoms which are component manifestations of emotions frequently reported during epileptic seizures. Nowadays, the underlying mechanism and location of brain areas involved in the processing of these sensations remain unclear. Our objectives were to characterize the type and frequency of visceral and emotional responses evoked by electrical stimulations, to produce a mapping of brain structures involved in their processing, and to assess the link between visceral sensations and emotional feelings. Methods: We reviewed 12, 088 bipolar stimulations performed in 203 patients during the presurgical evaluation of drug refractory epilepsy. Responses to stimulation were divided into viscero‐sensitive, viscero‐vegetative, and emotional sensations. Univariate analysis and conditional logistic regression were used to assess the association between visceral and emotional sensations and localization of the stimulated contacts. Results: In total, 543 stimulations evoked visceral and emotional sensations. Stimulations of operculo‐insulolimbic structures (amygdala, anterior and posterior insula, anterior and mid‐cingulate cortex, hippocampus, parahippocampus, temporal pole, frontal and parietal operculum) were significantly more associated with visceral and emotional sensations than all other cortical regions. Preferential implication of certain brain structures, depending on the type of visceral responses was evidenced: temporo‐mesial structures, insula, and frontoparietal operculum for viscero‐sensitive sensations; amygdala, insula, anterior and mid‐cingulate cortex, and temporal pole for viscero‐vegetative sensations; temporo‐mesial structures, anterior cingulate cortex, and frontal operculum for emotional sensations. Interpretation: Our data can help to guide SEEG explorations when visceral or emotional symptoms are part of the ictal semiology. They also bring some insights into the mechanisms of visceroception and the functional significance of the co‐localization of visceral and emotional representations in the human brain.